Fit of cobalt-chromium copings fabricated by the selective laser melting technology and casting method: A comparative evaluation using a profilometer - Koosha Gholamrezaei; Fariborz Vafaee; Behzad Fathi Afkari; Farnaz Firouz; Mozhgan Seif (Wolters Kluwer Medknow Publications, 2020)
Background: This study aimed to assess the marginal adaptation and internal fit of cobalt-chromium copings fabricated by the selective laser melting (SLM) and conventional techniques using a profilometer. Materials and Methods: In this in vitro study sample size was calculated to be a total of 10 in two groups (n = 5). A brass model was used that had a circular cross-section with a round shoulder margin with 0.5 mm thickness and axial walls with 10 mm length and 6° taper. The copings fabricated with both techniques (SLM and casting method) were placed on the model, and vertical marginal gap was measured using a profilometer. The internal fit of copings was assessed by weighing the light-body addition silicone applied inside them, which simulated the cement. Data were analyzed through parametric (Independent t-test) and nonparametric (Mann-Whitney U-test, Bootstrap, Spearman, and Pearson Correlation) analysis. All analyses were performed at a significant level (α = 0.05) using SPSS. Results: The mean marginal gap in the casting group (132.93 ± ) was significantly higher than that in the SLM group (67.14 ± 15.67 μm) (P < 0.05). The mean weight of light-body silicone was 9.60 ± in the SLM and 8.70 ± 1.21 mg in the casting group. No significant difference was noted between the two groups regarding the internal fit (P > 0.05). Conclusion: The copings fabricated by the SLM technique showed a smaller vertical marginal gap compared to the casting group. However, the two groups were not significantly different in terms of internal fit.